AVALIAÇÃO PÓS-OCUPAÇÃO DE PRÉDIOS COMERCIAIS NO SISTEMA LIGTH STEEL FRAMING EM BELÉM-PA - Silva, Luiz Felipe A.; Leão, Luis Inácio F.; Maués, Luiz Maurício F. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Light Steel Framing (LSF) building method, a prefabricated construction model, is very common in countries such as the USA. However, the using of this method in Brazil is mostly concentrated in the Southeast region, together with the production of the material. This research has as the main goal to perform a Post Occupancy Evaluation (POE) in buildings constructed using the LSF method in Belém, Pará. Based on the POE, it was held an interview with the users to qualitative evaluate some of the aspects of performance such as building aesthetic, usage and maintenance, thermal and acoustic comfort, satisfaction of the users and pathological manifestations. It was observed that LSF is a process that was accepted by the users, but there is still a lack of information about the building method in the region.